Celuk jewelry festivals as a catalyst for tourism-based creative economy: Managing cultural and economic capital in Bali - I Ketut Sida Arsa; I Made Mertanadi; Ni Made Ary Widiastini (International Journal of Applied Sciences in Tourism and Events, 2025)
The jewelry craft industry in Celuk Village, Bali, has long been recognized as a center of silver and gold craftsmanship that contributes significantly to the region’s tourism economy. This study analyzes the Celuk Jewelry Festival (CJF) as an event-based tourism initiative that not only promotes local products but also functions as a strategic platform for managing the interplay between cultural capital and economic capital. Using a qualitative approach with cultural studies and Bourdieu’s framework of habitus, field, and capital, the research explores how craftsmen, entrepreneurs, and local government negotiate their roles within the dynamics of production, distribution, and consumption. Findings indicate that the CJF strengthens Celuk’s brand image as a jewelry hub, enhances market access for local craftsmen, and creates opportunities for innovation while facing challenges of technology-driven reproduction and global competition. The study concludes that events such as the CJF act as catalysts for sustaining the creative economy in tourism villages, balancing tradition and innovation, and positioning cultural heritage as a competitive advantage in the global market.